Nitric oxide coordinates development of genomic instability in realization of combined effect with ionizing radiation - Mikhailenko, V.M.; Diomina, E.A.; Muzalov, I.I.; Gerashchenko, B.I. (Experimental Oncology, 2013)
The aim of this study was to investigate the ability of environmental nitrogen oxides or natural nitric oxide (NO) donors to modify free radicals balance and development of genomic instability alone or in combination with ionizing radiation. Methods: Genotoxicity and cytogenetic abnormalities were assessed in vitro in peripheral blood lymphocytes (PBL) isolated from healthy humans or in vivo in rats PBL. Human PBL were treated with physiologically relevant NO donor — S-Nitrosoglutathione and X-ray irradiation. The inhalation treatment of animals with NO was carried out in chamber with purified gaseous NO mixed inside with air. Levels of S-Nitrosohemoglobin and methemoglobin in the blood were assessed with electron paramagnetic resonance. The total level of reactive oxygen and nitrogen species in PBL was determined fluorometrically, and serum levels of reactive oxygen species was determined by spectrophotometric assay. DNA damages were assessed by alkaline single-cell gel electrophoresis. The frequency of chromosomal aberrations in human PBL measured with the conventional cytogenetic assay in metaphase cells on short-term (52 h) and long-term (72 h) cultures. Results: Environmental nitrogen oxides or release of NO from stable complexes with biomolecules (such as S-Nitrosothiols) intensified generation of free radicals, DNA damage and development of genomic instability alone or in combination with ionizing radiation. Treatment of PBL by S-Nitrosoglutathione caused prevalent induction of chromatid type but irradiation — chromosome aberrations. The dose dependence of chromatid-type aberrations observed in human PBL after combined influence of S-Nitrosoglutathione and ionizing radiation indicates a crucial role of NO in the formation of chromosomal instability. Conclusion: NO can deregulate free radicals balance resulted in genotoxic effect, posttranslational modification of repair enzymes and thus coordinated development of genomic instability and increase of cancer risk.